Analysis of climate indices and impacts on the rainfall regime in the Sub-medium stretch of the São Francisco River Basin, Brazil - Assis, Janaina Maria Oliveira de (2022)
This article covers the trends in climate changes in the semiarid region of the Northeastern region of Brazil, with a spacial cutout to the sub-medium stretch of the São Francisco River Basin. As a methodology, the RClimdex software was used to calculate the climate extremes indices of precipitation for the period between 1964 and 2016. The results indicated changes in the rainfall patterns, denoting an increase in the number of consecutive dry days, a reduction of the total annual rainfall, and also exhibiting negative trends in the daily rainfall intensity, in the number of days with moderate, strong, and intense rain, in the number of very humid and extremely humid days, contributing to the recurrent droughts in the semiarid region of Northeastern Brazil.